Practitioner research and the challenges of the good teaching canon in multilingual and multicultural globalized society - Costantino, Anna; Slimani-Rolls, Assia (Universidade do Estado do Rio de Janeiro, 2018)
This article seeks to respond to some of the tensions that face language teacher educators in globalized society. For teachers, an increasingly diverse, multicultural and multilingual globalized world means having to acknowledge diversity in their daily pedagogy, while confronting inequality in the distribution of learning resources and the demands of ever- bureaucratized educational settings. Even when theory indicates spaces for the enactment of local pedagogies responding to those challenges, teachers are unable to translate academic-based research into practice. This article argues for practitioner enquiry, practiced by the authors as Exploratory Practice (ALLWRIGHT & HANKS, 2009; HANKS, 2015a; SLIMANI-ROLLS & KIELY,2014), as an instance of how the empowering spaces suggested by theory can indeed be enacted as lived educational experience.